Dampak Kecerdasan Buatan terhadap Kemampuan Menulis Mahasiswa Bahasa Inggris: Tinjauan Literature yang Sistematis - Fira Fira; Ilham Ilham; Rima Rahmaniah (Universitas Muhammadiyah Mataram, 2025)
Abstract: The rapid development of artificial intelligence (AI) has brought significant transformation in the world of education, especially in the development of writing skills of English language students. This research aims to analyze the impact of AI on the writing skills of English students through a Systematic Literature Review (SLR) approach. Literature was collected from indexed databases such as Google Scholar, DOAJ, and Scopus within the last 10 years (2013-2024), using relevant keywords. Data analysis techniques were thematic to identify patterns, challenges, and opportunities in the application of AI in learning to write. The results showed that AI plays a role in improving writing skills through automatic feedback, personalized learning, and improved grammar accuracy. However, challenges such as technology dependency, academic ethics, and AI's limitations in understanding academic language contexts remain major concerns. To optimize the benefits of AI, a balanced teaching strategy between technology utilization and direct guidance from lecturers is required. This study provides insights into the integration of AI in writing instruction as well as recommendations for educators in effectively implementing this technology.Abstrak: Perkembangan kecerdasan buatan (AI) yang sangat pesat telah membawa perubahan yang signifikan dalam dunia pendidikan, khususnya dalam pengembangan kemampuan menulis siswa bahasa Inggris. Penelitian ini bertujuan untuk menganalisis dampak AI terhadap kemampuan menulis mahasiswa bahasa Inggris melalui pendekatan Systematic Literature Review (SLR). Literatur dikumpulkan dari database yang terindeks seperti Google Scholar, DOAJ, dan Scopus dalam 10 tahun terakhir (2013-2024), dengan menggunakan kata kunci yang relevan. Teknik analisis data dilakukan secara tematik untuk mengidentifikasi pola, tantangan, dan peluang dalam penerapan AI dalam pembelajaran menulis. Hasil penelitian menunjukkan bahwa AI berperan dalam meningkatkan kemampuan menulis melalui umpan balik otomatis, pembelajaran yang dipersonalisasi, dan peningkatan akurasi tata bahasa. Namun, tantangan seperti ketergantungan teknologi, etika akademik, dan keterbatasan AI dalam memahami konteks bahasa akademis masih menjadi perhatian utama. Untuk mengoptimalkan manfaat AI, diperlukan strategi pengajaran yang seimbang antara pemanfaatan teknologi dan bimbingan langsung dari dosen. Penelitian ini memberikan wawasan tentang integrasi AI dalam pengajaran menulis serta rekomendasi bagi para pengajar dalam menerapkan teknologi ini secara efektif.